RECRUITMENT PATTERN OF JUVENILE FISHES INTO PAMI RIVER ESTUARY (WEST PAPUA, INDONESIA - Suharti, Sasanti R.; Sugeha, Hagi Yulia (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
Recruitment pattern of juvenile fishes into Pami River estuary, West Papua, Indonesia (S 00.80970, E.134.06050), was studied from July to October 2005. The study purposes were 1) to observe fish diversity in family level, 2) to observe fish abundance of each family, 3) to observe recruitment pattern related to abundance and tidal rhythm. Samples were collected using line transect method and identification procedure were done based on morphological characteristics. A total of 19 Families were identified, namely Acanthuridae, Ambassidae, Anguillidae, Apogonidae, Carangidae, Chlopsidae, Clupeidae, Congeridae, Elopidae, Engraulidae, Gerreidae, Gobiidae, Mugillidae, Platycephalidae, Callyonimidae, Siganidae, Syngnathidae, Terapontidae, Tetraodontidae. Fishes composition varied each month.Â Family of Gobiidae was the most dominant juvenile fishes recruiting during this study with 32%, 69.5%, 84.3%, 71.3%, respectively. Other 8 families (Ambassidae, Engraulidae, Elopidae, Chlopsidae , Siganidae, Syngnathidae,Â Congeridae , and Callyonimidae) had the lowest composition varied from 0.4% to 3.2%. Three different patterns in abundance during the recruitment time of juvenile fishes, 1) early night (18.00-21.00) was represented by Ambassidae, Chlopsidae, Clupeidae, Gerreidae, Terapontidae, 2) mid-night (22.00-01.00) was represented by Callyonimidae, Congeridae, Engraulidae, Mugilidae, Platycephalidae, Tetraodontidae, and 3) late night (02.00-05.00) represented by Acanthuridae, Apogonidae, Carangidae, Elopidae, Gobiidae, Siganidae, Syngnathidae. However, the peak of abundance occurred at late night (>50 specimens caught), and recruitment pattern of all juvenile fishes has been associated with tidal rhythm.